Desenvolvimento de sistemas nanoestruturados mucoadesivos como potencial estratégia para o tratamento de câncer colônico - Brito, Natalia Araújo Pereira de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The development of nanostructured systems based on natural polysaccharides from polyelectrolyte complexation (PC) is a rational strategy for the colon-specific drug release. In this work, nanoparticles (NPs) based on the gellan gum (GG) and chitosan (QS), containing the antibiotic polymyxin B (PB) were obtained. Initially, the best polymer ratios and the influence of the order addition of the polymers (GG and QS) to obtain the NPs were evaluated. The formed systems showed high values of zeta potential (ZP) (between 24.37 mV - 41.23 mV), indicating their physical stability. It was found the GG addition to the QS dispersion led to the formation of smaller particles (between 575.30 nm - 974.60 nm), whereas the addition of QS to the GG dispersion formed larger particles (between 1,762.33 nm - 27,673.33 nm). In this way, were selected for incorporation of PB the samples obtained with the addition of GG to the dispersion of QS. After incorporation, the NPs presented mean diameter in the range of 471,25 nm - 1,255,85 nm and positive values of PZ (between 35,14 mV - 38,93 mV). The analysis by infrared spectroscopy (IR) evidenced the formation of NPs through the possible interactions between the functional groups -OH, -COOH and -NH2 of the polyelectrolytes. The structural characteristics of systems was evaluated by X-ray diffraction (XRD) in the data indicated the formation of more organized structures with a higher degree of crystallinity. The high resolution scanning electron microscopy (SEM) analysis revealed the existence of nanometric scale particles, with regular, spherical and apparently smooth surfaces. The mucoadhesive capacity of the systems... (Complete abstract click electronic access below)

O desenvolvimento de sistemas nanoestruturados baseados em polissacarídeos naturais a partir da complexação polieletrolítica (CP) constitui uma estratégia racional para a liberação cólon-específica de fármacos. Neste trabalho, foram obtidas nanopartículas (NPs) baseadas em goma gelana (GG) e quitosana (QS), contendo o antibiótico polimixina B (PB). Inicialmente, foram avaliadas as melhores proporções poliméricas e a influência da ordem de adição dos polímeros (GG e QS) para obtenção das NPs. Os sistemas formados apresentaram elevados valores de potencial zeta (PZ) (entre 24,37 mV - 41,23 mV), indicando sua estabilidade física. Foi verificado que a adição da GG à dispersão de QS levou a formação de partículas menores (entre 575,30 nm - 974,60 nm), enquanto que a adição de QS à dispersão de GG formou partículas maiores (entre 1.762,33 nm - 27.673,33 nm). Dessa maneira, foram selecionadas para incorporação da PB as amostras obtidas com a adição de GG à dispersão de QS. Após a incorporação da PB, as NPs apresentaram diâmetro médio na faixa de 471,25 nm - 1.255,85 nm e valores positivos de PZ (entre 35,14 mV - 38,93 mV). A análise por meio da espectroscopia de absorção na região do infravermelho (IV) evidenciou a formação de NPs, através das possíveis interações entre os grupos funcionais -OH, -COOH e -NH2 dos polieletrólitos. As características estruturais dos sistemas foram avaliadas por DRX e os dados indicaram a formação de estruturas mais organizadas e com maior grau de cristalinidade. A análise por microscopia eletrônica de varredura de alta resolução (MEV-FEG) evidenciou a formação de partículas em escala nanométrica... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Nanopartículas; Nanoestruturas; Cólon (Anatomia) - Câncer; Polissacarideos; Quitosana; Colon (Anatomy) Cancer